Auto Vulnerability Assessment and PenetrationTesting Tools - et. al., Mr Vishal Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The complexness of the system is increasing day by day. This results in a lot of vulnerability for Systems. The attackers use these being in danger of exploiting the victim's system. it's best to sight this danger earlier than time for the assailant. Attack risk assessment is usually under estimated. While Risk Assessment and Entry check will be used as cyber-defense technology to supply effective cyber protection. during this paper we've got shown that Vulnerability Assessment and Penetration Testing (VAPT) as a cybersecurity technology, on however we are able to give effective cyber protection penetration Vulnerability Assessment and Login check. we've got outlined the entire life cycle of Vulnerability Assessment and Penetration Testing in systems or networks and actions taken to resolve that risk and to prevent potential attacks. during this paper we've got explained customary risk assessment methods and alternative in style VAPT tools.